Illegal Migration And Human Trafficking - AZAMATOVA, GULMIRA (The journal of contemporary issues in business and government, 2021)
This article discusses illegal migration and human trafficking and analyzes the results and discussions on this topic. Migration is a very ancient phenomenon, a process involving several circumstances that lead to a change in the place of residence of the population. Currently, the development of this process in various disciplines and directions is studied scientifically. Laws and concepts in the field of migration were first scientifically introduced in 1885 by the German-English scientist Ernst-Georg Ravenstein. He created the “law of migration” at the end of the 19th century. According to these laws, migrants leave one region with disabilities and settle in other regions with greater opportunities [2].